Isolation of sources of resistance of winter wheat samples to the group of pathogens as a component of immunological protection of plants - Golosna, L.; Afanasieva, O.; Lisova, G.; Kucherova, L. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
In 2014—2016 on the artificial infectious background of the pathogens of Septoria leaf blotch, leaf rust and bunt, and on the natural background of powdery mildew and root rot, the stability of the collection of cultivars of winter wheat of different ecological and geographical origin was assessed. Perspective sources of group resistance to pathogens are identified to powdery mildew and root rot — Midas (Austria); to pathogens of powdery mildew and bunt — Radiance (Ukraine), Miranda (Romania), F94578G3-1/Bucur // Delabrad (Romania); to leaf rust and root rot — Mukhran (Germany) and Mv17/Zrn (Iran). To the pathogen Septoria leaf bloth of winter wheat resistant varieties is not detected.